Efektivitas Penggunaan Teknologi Berbasis Komputer melalui Speech-to-Text dan Aplikasi Elsa Speak dalam Meningkatkan Kemampuan Speaking Siswa pada Pembelajaran Bahasa Inggris di Universitas Bina Sarana Informatika - Meiva Eka Sri Sulistyawati; Eri Riana; Adianta Sebayang (Journal of Innovative and Creativity, 2025)
This study aims to analyze the effectiveness of the use of computer-based technology through speech-to-text and the Elsa Speak application in improving students' speaking skills in English learning at Bina Sarana Informatika University. This study uses a qualitative case study approach to examine the effectiveness of speech-to-text technology and the ELSA Speak application in improving students' speaking skills at Bina Sarana Informatika University through the collection of observation, interview, and documentation data. Data analysis was carried out using the Miles and Huberman model continuously to produce valid conclusions regarding the improvement of English speaking skills through this technology. The results of this work, namely the use of computer-based technology, namely the speech-to-text feature and the ELSA Speak application, have proven effective in improving UBSI students' English speaking skills. This technology helps students practice pronunciation and intonation independently with direct feedback that facilitates pronunciation improvement. The use of both applications makes learning more interesting, interactive, and in accordance with students' learning styles, thereby increasing clarity of pronunciation and self-confidence. Institutionally, this digitalization of learning supports the campus' vision in improving the quality of education and equalizing access to learning in the digital era.